Analysis of Social Change Due to Tourism Development in Ciwaru Village, Ciemas Sub-District, Sukabumi District - Rikar Abdan Syakuuro; Winarno Winarno (ARISTO, 2024)
Human civilization undergoes dynamic development in tandem with the intricate changes embedded in the fabric of human existence. These changes, inherently tied to human life, are referred to as social changes. It is essential to recognize that the impact of social change is not confined to a single dimension; rather, it radiates across various sectors, creating a ripple effect. This implies that alterations in the social landscape resonate in diverse fields, prominently seen in tourism. Specifically, the social changes in Ciwaru Village, stemming from the advancement of Global Geopark tourism, exemplify this interconnected evolution. This study adopts a descriptive research approach, focusing on Ciwaru Village in the Ciemas Sub-district of Sukabumi Regency. Employing a closed questionnaire as the primary data collection tool, the research delves into the perspectives of the local community. The analysis reveals that 76% of Ciwaru villagers endorse the social changes brought about by tourism development. The establishment of the Global Geopark has significantly influenced social dynamics in Ciwaru Village. This impact manifests in alterations to social interactions, shifts in attitudes and social values, and modifications to behavior patterns within the community. The inauguration of the Global Geopark emerges as a catalyst for transformative social changes in Ciwaru Village, illustrating the interconnected nature of human society and its evolution in response to external influences